Chromosomal analysis of Astyanax fasciatus (PISCES, CHARACIDAE) from the Araguari river, Uberlândia, MG, Brazil - Torres-Mariano,A. R. (2006)
The genus Astyanax is one of the most numerous of the family Characidae, comprising a large number of similar-shaped species, but displaying innumerable karyotypic variations in its chromosome number and/or structure. The literature describes A. fasciatus populations with diploid chromosome numbers varying from 2n = 45 to 2n = 48. In this study, A. fasciatus specimens captured in the Araguari River (Alto Paraná basin) were cytogenetically characterized, revealing a diploid chromosome number of 2n = 46. The nucleolar organizing regions (NORs), detected with silver nitrate staining, showed a multiple system with two pairs of marked chromosomes. These findings are congruent with those of other studies involving populations of the same species.